2015 President's Plenary International Psycho‐oncology Society: psychosocial care as a human rights issue—challenges and opportunities. Issue 4 (17th August 2016) - Travado, Luzia; Breitbart, William; Grassi, Luigi; Fujisawa, Daisuke; Patenaude, Andrea; Baider, Lea; Connor, Stephen; Fingeret, Michelle
Abstract: The International Psycho‐Oncology Society (IPOS) Human Rights Task Force has been working since 2008 to raise awareness and support, for the relevance of psychosocial cancer care as a human rights issue. In 2014 the "Lisbon Declaration: Psychosocial Cancer Care as a Universal Human Right" was fully endorsed by IPOS. Subsequently, the IPOS Standard on Quality Cancer Care, endorsed by 75 cancer organizations worldwide, has been updated and now includes 3 core principles: Psychosocial cancer care should be recognised as a universal human right; Quality cancer care must integrate the psychosocial domain into routine care; Distress should be measured as the 6th vital sign. The President's plenary held at the 2015 World Congress of Psycho‐Oncology in Washington DC was devoted to discussing psychosocial care as a human rights issue. Many challenges and opportunities are illustrated in different continents and contexts: from Africa where resources for basic cancer treatment are scarce and children and their parents face significant difficulties with hospital detention practices; to Europe where for many countries psychosocial care is still seen as a luxury; and the Middle East where Muslim women face stigma and a culture of silence over cancer. We further discuss how to move the Lisbon Declaration forward towards its implementation into clinical practice globally, using the successful example of the World Health Assembly resolution supporting palliative care as a human right which has achieved widespread approval, and identifying the vital role the IPOS Federation of National Psychoncology Societies plays worldwide to move this agenda forward.